Application Considerations for Successful Use of VIF and Metalized Mulches with Reduced Fumigant Rates in Tomato - Jim Gilreath; Bielinski Santos; John Mirusso; Joe Noling; Phyllis Gilreath (EDIS)
This document is HS287, a publication of the Horticultural Sciences Department, Florida Cooperative Extension Service, IFAS, University of Florida. Published August 2005.